Analysis of factors influencing the qualitative characteristics of equine synovial fluid - TYRNENOPOULOU, P; DIAKAKIS, N; RIZOS, E; CHAINTOUTIS, S; PATSIKAS, MN; PAPADOPOULOU, P; AGGELI, A; POLIZOPOULOU, ZS; PAPAZOGLOU, L (Journal of the Hellenic Veterinary Medical Society, 2022)
The objective of the present study was to investigate the viscoelastic properties in synovial fluid between normal horses and horses with naturally occurring OA and to detect factors affecting synovial fluid viscosity. In total, 105 horses were included in this study. Synovial fluid samples were obtained from 60 mature horses with mild to moderate osteoarthritis in the 2nd interphalangeal, the metacarpophalangeal or the intercarpal joint. Forty-five horses were used as controls. Full rheological sample characterization was performed in order to measure the elastic G’ and viscous G’’ moduli. For determining hyaluronic acid concentrations a commercially available ELISA kit was used. The results of the linear mixed effect (LME) model revealed statistically significant (p < 0.001) effect of HA concentration, on the mean values of logG’ and logG” measurements. The ANOVA findings of the final model revealed statistically significant effect of joint type (p < 0.001) on the mean values of viscoelastic measurements. Interpreting the coefficients of the covariates osteoarthritis (p < 0.001) and age (p = 0.013), a negative correlation was detected on the response logG’ and logG” measurements. Geldings seemed to present lower viscous properties compared to mares. To the authors’ knowledge this is the first multivariate study to quantitatively evaluate the several factors that affect the viscoelastic properties of equine synovial fluid. Horses with osteoarthritis seemed to present lower viscoelastic properties compared to the healthy subjects that are joint type dependant. Finally, considering the multifactorial nature of osteoarthritis, one should expect an emerging need of personalized disease-modifying treatments.